IMMUNOLOGICAL ANALYSIS OF CHLAMYDIASIS IN SHEEP AND PATHOMORPHOLOGY CHANGES IN THE FETAL - Наврузов Н.И.; Исматова Р. А.; Джураев О. А.; Ҳамрақулов Н.Ш.; Сайфиддинов Б.Ф.; Актамов У. Б. (Web of Journals Publishing, 2025)
The results of an immunological analysis for chlamydia in pregnant women who suffered a miscarriage and had an abortion were found to be optically significant. A pathoanatomic examination of the internal organs of pregnant women who had an abortion at the age of 135-142 days showed that there were no histological data.
Keywords: Chlamydiosis, abot, fetus, Chlamydia abortus ovis, optical density, blood serum, internal organ, hematoxylin, eosin, dosator, chromogen, antitelo, immunoferment analysis, conjuncture, dystrophy, infiltration, myocardial, atelectasis.